Republic of Beliefs: An Experimental Investigation - Utteeyo Dasgupta; Fatos Radoniqi (Institute of Labor Economics (IZA), 2021)
The success of a country's anti-corruption policies can crucially depend on the citizens' beliefs about the existing legal environment. We test this key idea of Basu (2020) using a novel design which systematically manipulates beliefs of participants in an experiment. Our results suggest that Basu's "Republic of Beliefs" idea provides a critical insight in policy formulation; Merely introducing an anti-corruption law is not sufficient in aiding the country towards the desired equilibrium, especially in developing countries, where the existing legal enforcement machinery has severe scopes of leakages.
Keywords: C91; K42; 330; republic of beliefs; asymmetric punishment; harassment bribery; experiment